A clinical case of hypothalamic syndrome combined with Klinefelter syndrome - Kys , Maryna; Halushko, Yurii-Daniel; Yerokhovych, Viktoriia (The Ukrainian Scientific Medical Youth Journal, 2023)
the article describes a clinical case of a hypothalamic syndrome associated with a congenital disease - Klinefelter syndrome in a 21-year-old patient. Dysmetabolic complications were studied against the background of endocrine and genetic pathologies. Klinefelter syndrome was diagnosed in the patient at the age of 10, mosaic variant of karyotype 47XXY/46XY was detected. Against the background of a rare genetic pathology, signs of a hypothalamic puberty syndrome began to appear at the age of 15: acne, pink stretch marks on the lateral areas of the abdomen and breasts, gynecomastia, and excess weight. General clinical laboratory studies, carbohydrate metabolism indicators, sexual and thyroid hormones did not differ from reference values. The cortisol level in the blood was 23.4 mcg/dL, slightly exceeding the upper limit of the reference values (4.30-22.4 mcg/dL), indicating a state of mild hypercorticism. Manifestations of dysmetabolic cardiomyopathy were noted in the cardiovascular system, complicated by stable stage II arterial hypertension. The peculiarity of the clinical case is the combination of endocrine pathology with genetic pathology, which determines the specific appearance of the patient, and the presence of dysmetabolic complications without disturbances of carbohydrate metabolism in stage III obesity. The acceleration of puberty, which often occurs with the hypothalamic syndrome, did not occur due to the concomitant hypoandrogenic effect of Klinefelter syndrome. In the presence of hypothalamic syndrome in the patient, the late development of secondary sexual characteristics was noted, which is more characteristic of Klinefelter syndrome, but normal mental activity was preserved, which is rarely observed with the mosaic form of this genetic pathology. Another clinical feature is the absence of typical manifestations of hypogonadism in the post-pubertal period, which is confirmed by a normal level of male and female sex hormones in the blood, which is atypical. Due to the peculiarity of this clinical case, the patient’s fertility can be preserved. In addition to the existing dysmetabolic complications in the patient and metabolic syndrome, there is a high risk of developing type 2 diabetes, atherosclerosis, osteoporosis, and breast cancer, because Klinefelter syndrome and hypothalamic syndrome complicate each other. Therefore, it is important to study the issue of the combination of these two pathologies, possible consequences, and ways to overcome them to improve the patient’s clinical prognosis and quality of life.